ORGANIZATIONAL AND EDUCATIONAL ACTIVITY SOCIAL TEACHERS IN SECONDARY SCHOOLS: THEORETICAL ASPECTS - Ostrianko, Tetiana S. (Educological discourse, 2015)
The article reveals the essence of theoretical and methodological approaches to organizational and pedagogical activity of the social pedagogue of a secondary school. It is defined the content of organizational activities, and presents the author's vision of organizational and pedagogical activity of the school’s social pedagogue, which implies the involvement of all participants of training and educational processes to meet the challenges of social and educational activities. Interaction as the basis of organizational and pedagogical activity of the social pedagogue in a secondary school is allocated. The author described the components of organizational and pedagogical activity of a social pedagogue such as: organization, coordination, management.